2023
DOI: 10.1177/19253621231157933
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Eosinophilia Following Moderna COVID-19 Vaccine Administration: A Case Report

Abstract: Coronavirus disease 19 (COVID-19) vaccination is considered an important part in improving health outcomes globally. While various adverse events following vaccination against COVID-19 have been reported, eosinophilic diseases have rarely been documented in the literature and are poorly understood. Although vaccination is lauded as being “safe,” it has become apparent that adverse reactions related to the vaccines can have detrimental health effects for certain individuals. We present a case of a death related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Dear Editor, we would like to share ideas on the publication "Generalized Eosinophilia Following Moderna COVID-19 Vaccine Administration: A Case Report (1)." Hojberg et al describe a fatality caused by many severe preexisting comorbidities, aggravated by new-onset gastrointestinal problems that were temporally correlated with recent COVID-19 vaccination and did not subside, but worsened before death (1). Autopsy found signs of eosinophilic enteritis, linked with ascites, as well as eosinophilic inflammation elsewhere, including the lungs and heart, according to Hojberg et al (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, we would like to share ideas on the publication "Generalized Eosinophilia Following Moderna COVID-19 Vaccine Administration: A Case Report (1)." Hojberg et al describe a fatality caused by many severe preexisting comorbidities, aggravated by new-onset gastrointestinal problems that were temporally correlated with recent COVID-19 vaccination and did not subside, but worsened before death (1). Autopsy found signs of eosinophilic enteritis, linked with ascites, as well as eosinophilic inflammation elsewhere, including the lungs and heart, according to Hojberg et al (1).…”
mentioning
confidence: 99%
“…Hojberg et al describe a fatality caused by many severe preexisting comorbidities, aggravated by new-onset gastrointestinal problems that were temporally correlated with recent COVID-19 vaccination and did not subside, but worsened before death (1). Autopsy found signs of eosinophilic enteritis, linked with ascites, as well as eosinophilic inflammation elsewhere, including the lungs and heart, according to Hojberg et al (1). Hojberg et al concluded that the temporal relationship between vaccination, symptom onset/progression, and death, as well as the literature indicating a possible association between coronavirus vaccination and eosinophilic reactions lead to the conclusion that this death could have been caused by an adverse reaction to COVID-19 vaccination (1).…”
mentioning
confidence: 99%